A Pilot Study Assessing Left Ventricle Diastolic Function in the Parasternal Long-axis View - Mümin Murat Yazici; Nurullah Parça; Enes Hamdioğlu; Meryem Kaçan; Özcan Yavas¸i; Özlem Bilir (Western Journal of Emergency Medicine)
Introduction: Spectral Doppler echocardiography is used to evaluate diastolic dysfunction of the heart. However, it is difficult to assess diastolic function with this modality in emergency department (ED) settings. Based on the hypothesis that E-point septal separation (EPSS) measured by M-mode in the parasternal long-axis (PSLA) view may facilitate the assessment of diastolic function in emergency patient care, we aimed to investigate whether EPSS measured by M-mode in the PSLA view correlates with spectral Doppler assessment in patients with grade 1 diastolic dysfunction. Methods: We performed this prospective, observational, single-center study was performed in the ED of a tertiary training and research hospital. All patients who presented to the emergency critical care unit with symptoms of heart failure were evaluated by the cardiology department, had grade 1 diastolic dysfunction confirmed by the cardiology department, and did not meet any of the study’s exclusion criteria. The study population of 40 (included rate 14%) was formed after the exclusion criteria were applied to 285 patients who met these conditions. Patients included in the study underwent spectral Doppler measurements in the apical four-chamber (A4C) view followed by M-mode measurements in the PSLA view. We then compared the measurements. Results: The correlation between the early diastolic velocity of the mitral inflow to the late diastolic velocity (E/A) ratio in spectral Doppler measurements and the EPSS/ A-point septal separation (APSS) ratio in M-mode was strong (correlation coefficient 0.677, P = 0.001). Similarly, the correlation between E in spectral Doppler measurements and the EPSS/APSS ratio in M-mode measurements was also moderately strong (correlation coefficient 0.557, P = 0.001). Conclusion: A significant correlation exists between the M-mode EPSS/APSS ratio measurement in the PSLA view and the spectral Doppler E/A ratio measurement in the A4C window to evaluate grade 1 diastolic dysfunction. This association suggests that M-mode measurements in the PSLA may be used in diastolic dysfunction.